2020
DOI: 10.1111/pirs.12503
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the spatial dimension to inequality: A counterfactual analysis for OECD countries

Abstract: This paper provides recent evidence on the contribution of the spatial dimension to inequality and more specifically accounts for the impact of the changes in the territorial distribution of the population on the recent dynamics of income inequality. We use LIS harmonized microdata for a selected sample of OECD countries. We provide new evidence over a more varied group of countries and a more recent period than in previous studies. We perform different types of decompositions to isolate the contribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Among determinants of income inequality reductions, instead, the evidence strictly follows the classical Heckscher-Ohlin framework, suggesting that population movements help minimizing, if not inverting, inequality trends (Ayala et al, 2019). Decreasing population movements may reverse such trends: Ganong and Shoag (2017) explain the substantial decline in income convergence rates across US states by means of a model whereby rising land rent in high-income areas deter low-skilled migrants from in-migrating, thus ultimately causing a slow-down in income convergence.…”
Section: Income Inequalities At the City Levelmentioning
confidence: 95%
See 1 more Smart Citation
“…Among determinants of income inequality reductions, instead, the evidence strictly follows the classical Heckscher-Ohlin framework, suggesting that population movements help minimizing, if not inverting, inequality trends (Ayala et al, 2019). Decreasing population movements may reverse such trends: Ganong and Shoag (2017) explain the substantial decline in income convergence rates across US states by means of a model whereby rising land rent in high-income areas deter low-skilled migrants from in-migrating, thus ultimately causing a slow-down in income convergence.…”
Section: Income Inequalities At the City Levelmentioning
confidence: 95%
“…Secondly, the conceptual link between smartness and income inequalities at the urban level can be understood as a consequence of adopting technologies that cannot be afforded and exploited by low-income citizens, thus leading to the worsening of inequalities. Since income inequality has an inherently spatial nature (Ayala et al, 2019) this prompts us to link this to urban smartness, which is another space-varying factor. In detail, some of the Smart solutions might be difficult to access by some segments of the population (mainly identified by the lower income segment of the population), thus further widening the gap between the wealthy and the lowerincome population.…”
Section: Smart Cities: Definitions and Relation To Income Inequalitiesmentioning
confidence: 99%
“…It has also been shown that households' gross income inequalities are affected mainly by the impact of labour share. However, most researchers (Ayala et al, 2019;Gil-Anala et al, 2019;Zungu et al, 2021) focused strictly on macroeconomic factors, ignoring the influence of the labour share on the national income. As for the control factors, such as government consumption (Madzinova, 2017), GDP per capita, and GDP growth (Afonso et al, 2008), the direction of their impact coincides with those obtained by other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…La distribución de la renta es un elemento esencial del bienestar de la población y está directamente ligada al estudio de la desigualdad, cuestión que, tras la última crisis económica y financiera, ocupa un lugar aún más central en la agenda científica y política internacional (Ayala, Martín & Vicente, 2020;Castells-Quintana, Ramos & Royuela, 2015;EU, 2019;OECD, 2015). El caso de España es especialmente grave en el contexto europeo: por una parte, desde mediados de los noventa y hasta la crisis de 2007 la desigualdad no se logró reducir a pesar de ser este un periodo caracterizado por una fuerte expansión económica y un intenso crecimiento del empleo.…”
Section: Análisis Tradicionales De La Distribución De La Renta De Los Hogares En Españaunclassified